A Resilience‐Based Intervention Programme to Enhance Psychological Well‐Being and Protective Factors for Rural‐to‐Urban Migrant Children in China. Issue 1 (9th July 2019) - Tam, Cheuk Chi; Li, Xiaoming; Benotsch, Eric G.; Lin, Danhua
Abstract: Background: The current study evaluated the preliminary efficacy of a pilot trial of a resilience‐based intervention programme designed to decrease depression symptoms and improve protective factors (e.g. personal assets, social resources, cultural adaptation self‐efficacy, interpreting adversity, and self‐esteem) among rural‐to‐urban migrant children in China. Methods: Participants were 285 fourth and fifth graders from two migrant children schools in Beijing. One school was cluster‐randomly assigned as the intervention group ( n  =   127) and the other was assigned as the wait‐list control group ( n  =   158). Data were collected at baseline and post‐intervention with a follow‐up rate of 96.8 per cent. Results: Multivariate analyses found significantly greater increases in social resources, cultural adaptation self‐efficacy, and making positive sense of adversity in the intervention group than in the control group. In the intervention group, migrant children who had moved more often reported a higher increase in personal assets than those who had fewer mobility experience. Conclusion: The findings suggest that the resilience‐based intervention can be efficacious in improving resilience among migrant children in China.